(untitled) (Journal of Parents and Teachers, 2014)
A group of teachers conducted a study on the barriers and possible alternatives for all students to learn. Some of them are the Educational Administration, the educational organization, the organization of the classroom, or the family, and in all cases they explain alternatives that lead to a good learning.